Asymmetric spillovers in ASEAN bond markets - Muhammad Yahya; Tianqi Luo; Mohammed Gazi Salah Uddin; Donghyun Park; Shu Tian; Ranadeva Jayasekera (Asian Development Bank (ADB), 2023)
The financial markets of members of the Association of Southeast Asian Nations (ASEAN) have become increasingly integrated with regional and global markets. ASEAN economies also exhibit strong trade connectedness and interdependence with regional and global business cycles. Such connectedness can foster the spread of global shocks to ASEAN members and distress local financial markets. Global shocks, such as financial crises or commodity price changes, can have asymmetric and nonlinear effects on other financial and commodity markets around the world. This paper aims to estimate and evaluate the intensity and directionality of bond market connectedness between ASEAN and major regional and global markets. Furthermore, we aim to identify factors impacting the interconnectedness dynamics among these markets. This study derives an uncertainty connectedness measure grounded on the attributes of static and dynamic dependence frameworks and empirically evaluates its role in transmitting or receiving shocks based on various information spillover and contagion channels. The findings of this study have important implications for market participants, regulators, and policymakers.
Keywords: E52; E58; F42; 330; asymmetric spillover; uncertainty; connectedness; ASEAN